Genetic relationships among Malaysian banana cultivars revealed by chloroplast SSR - Tee, Meng Han; Daud, Siti Khalijah (2009)
Bananas and plantains have been highly esteemed and widely used by man since ancient times. Fiber contents in bananas and plantains act as an aid for digestion. There are also reports that ripe bananas are used in the treatment of asthma and bronchitis. In breeding programs, the breeds valued characteristics should be maintained during its further improvement. A Chloroplast Simple Sequence Repeat (SSR) analysis was carried out to determine variation and relationships among local banana cultivars. Eight banana cultivars were used in this study, namely Mas (AA), Berangan (AAA), Raja (AAB), Rastali (AAB), Awak (ABB), Nipah (BBB), Kapas (AA) and Nangka (AAB). Twenty five individuals of each cultivar were collected from Perak, Selangor, Johor, Pahang Kedah, Kelantan and Negeri Sembilan. Sixteen Microsatellite primer pairs were selected to amplify the chloroplast DNA. The highest genetic distance was found between Pisang Nipah and Pisang Raja (0.0654) whilst the lowest was between Pisang Berangan and Pisang Awak (0.0036). The dendrogram showed that Pisang Raja and Pisang Rastali were grouped together and they are of similar genotypes. However, Pisang Awak and Pisang Berangan have the lowest genetic distance and grouped together although their genotypes are different. The results of this study suggest that the clustering of these bananas does not necessarily follow their ploidy levels.